2017
DOI: 10.3324/haematol.2017.175687
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the anion exchanger 2 with specific peptides as a new therapeutic approach in B lymphoid neoplasms

Abstract: Regulatory T (Treg) cells can weaken antitumor immune responses, and inhibition of their function appears to be a promising therapeutic approach in cancer patients. Mice with targeted deletion of the gene encoding the Cl−/HCO3− anion exchanger AE2 (also termed SLC4A2), a membrane-bound carrier involved in intracellular pH regulation, showed a progressive decrease in the number of Treg cells. We therefore challenged AE2 as a potential target for tumor therapy, and generated linear peptides designed to bind the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The acidic tumor microenvironment promotes an anti-inflammatory T-cell response (see section 5.6.1), but the deletion of AE2 promotes a pro-inflammatory T-cell response (see section 4.12.1). Therefore inhibition of T-cell AE2 could be a valuable paradigm for enhancing a cytotoxic immune response [435] .…”
Section: Other Applications By Clinical Specialtymentioning
confidence: 99%
“…The acidic tumor microenvironment promotes an anti-inflammatory T-cell response (see section 5.6.1), but the deletion of AE2 promotes a pro-inflammatory T-cell response (see section 4.12.1). Therefore inhibition of T-cell AE2 could be a valuable paradigm for enhancing a cytotoxic immune response [435] .…”
Section: Other Applications By Clinical Specialtymentioning
confidence: 99%
“…Accumulating evidence suggests that AE2 is involved in tumorigenesis. Celay et al addressed the role of AE2 and its target peptide reduced tumor growth in vivo [30]. Enhanced AE2 promotes ovarian cancer progression by activating mTOR signaling [17]; whereas, reduction of AE2 enhances cellular migration via the activation of MMP pathways in the esophageal squamous cell carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, in PBC, AE2 mRNA levels are decreased not only in the liver but also in peripheral lymphoid cells [ 43 ▪▪ ]. Thus, altered pHi because of defective AE2 activity may affect the function of immune cells in PBC patients [ 48 , 89 ]. Indeed, we found that Ae2a,b -deficient mice exhibit reduced Treg population, progressive expansion of CD8 + T cells and increased production of IL-12 and IFNγ [ 46 , 47 ].…”
Section: The Role Of Ae2 Deficiency In the Dysregulation Of Immune Rementioning
confidence: 99%